Dengue virus M and E proteins belonging to genotype II (Cosmopolitan) of serotype 2 are influenced by the nature of M residue 36 - Decotter, Jason; Desprès, Philippe; Gadea, Gilles (Journal of general virology, 2023)
Mosquito-borne dengue disease is caused by the dengue virus serotype-1 to serotype-4. The contemporary dengue outbreaks in the southwestern Indian ocean coincided with the widespread of dengue virus serotype 2 genotype II (Cosmopolitan), including epidemic viral strains DES-14 and RUN-18 isolated in Dar es Salaam (Tanzania) in 2014 and La Reunion Island (France) in 2018, respectively. Heterodimeric interaction between prM (intracellular precursor of surface structural M protein) and envelope E proteins is required during the initial stage of dengue virus assembly. Amino acid 127 of DES-14 prM protein (equivalent to M36) has been identified as an infrequent valine whereas RUN-18 has a common isoleucine. In the present study, we examined the effect of M-I36V mutation on the expression of a recombinant RUN-18 E protein co-expressed with prM in human epithelial A549 cells. The M ectodomain of dengue virus serotype 2 embeds a pro-apoptotic peptide referred as D 2 AMP. The impact of M-I36V mutation on the death-promoting capability of D 2 AMP was assessed in A549 cells. We showed that valine at position M36 affects expression of recombinant RUN-18 E protein and potentiates apoptosis-inducing activity of D 2 AMP. We propose that the nature of M residue 36 influences the virological characteristics of dengue 2 M and E proteins belonging to genotype II that contributes to global dengue burden.